Pengaruh Disiplin terhadap Kinerja Para Medis Ruang Perawatan Bedah pada RSUD Raden Mattaher Jambi - Azizah Azizah (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
The method used in this research is quantitative descriptive method by using statistical formula to help analyze data obtained from the field. The data in this research is obtained by distributing questionnaires to 43 respondents who become the sample. Then processed using Product Moment correlation formula, and assisted with soft ware computer that is SPSS 24 to know there is a relationship between discipline and performance. The result of the research shows that the test regression equation test have positive direction toward employee performance with significant level is proved tcount 3,893>ttable 2.0195 in other words have close enough relationship with performance. For a correlation calculation of 0.519, this indicates a positive relationship between discipline and performance. Furthermore, the determinant coefficient obtained by 27%, the rest of 73% influenced by other factors outside the study of this study.